WASTEWATER-BASED EPIDEMIOLOGY FOR TUBERCULOSIS SURVEILLANCE IN VIETNAM: SCIENTIFIC BASIS AND POTENTIAL APPLICATIONS (Vietnam Journal of Community Medicine, 2026)
Tuberculosis (TB) continues to pose a major public health concern in Vietnam, with a high disease burden. Traditional epidemiological surveillance systems, which primarily rely on clinical data, may not fully reflect the true prevalence of tuberculosis in the community. Wastewater-based epidemiology (WBE) is increasingly recognized as a useful method for monitoring population-level health trends, enabling the proactive and cost-effective assessment of pathogen presence and circulation trends at the community level. This narrative review evaluates the feasibility of WBE for tuberculosis surveillance in Vietnam by synthesizing and analyzing existing scientific evidence on TB. Recent studies have demonstrated that Mycobacterium tuberculosis has been reported in wastewater, and bacterial signals in wastewater are associated with the TB burden in communities. However, the implementation of WBE for TB surveillance still faces several technical challenges, including low bacterial concentrations, limitations of current recovery methods, and constraints related to wastewater infrastructure in Vietnam. Based on these findings, this paper proposes future research idea and practical implementation strategies, underscoring the potential of WBE as a complementary approach to enhance surveillance capacity and support tuberculosis prevention and control efforts in Vietnam.
Keywords: Wastewater-based epidemiology (WBE), Mycobacterium tuberculosis, wastewater, Vietnam